Susceptibility and resistance of brook lamprey, Lampetra planeri (Bloch), roach, Rutilus rutilus (L.) and perch, Perca fluviatilis L. to Gyrodactylus salaris Malmberg (Monogenea) - Tor A. Bakke; Peder A. Jansen; Åge Brabrand (Fauna Norvegica)
The susceptibility and resistance of brook lamprey, Lampetra planeri, roach Rutilus rutilus and perch, Perca fluviatilis to Gyrodactylus salaris were examined. The level of resistance to the parasite was assessed from counts, made on anaesthetized hosts, of the numbers of G. salaris after an initial experimental exposure to salmon infected with G. salaris. The results of four experiments carried out at constant temperature (11.5°C). and decreasing temperatures (11.5°C - 0.7°C), demonstrated that G. salaris attached to the potential hosts but showed no sign of reproduction. The parasites were eliminated within 2 - 4 days. The three host species tested were clearly highly resistant to G. salaris. The restricted attachment frequency and resistance observed, indicate that these fish species play an insignificant role in the dissemination of the parasite.